Intake patterns and dietary associations of soya protein consumption in adults and children in the Canadian Community Health Survey, Cycle 2.2. Issue 2 (6th January 2015) - Mudryj, Adriana N.; Aukema, Harold M.; Yu, Nancy
Abstract : Soya foods are one of the recommended alternatives to meat in many dietary guidelines. While this is expected to increase the intake of some nutrients, potential concerns regarding others have been raised. The purpose of the present study was to examine the prevalence and the association of soya food consumption with nutrient intakes and dietary patterns of Canadians (age ≥ 2 years). Cross-sectional data from the 2004 Canadian Community Health Survey (Cycle 2.2; n 33 218) were used to classify soya consumers and non-consumers. Soya consumers were further divided into two groups based on their soya protein intake. Sample weights were applied and logistic regression analysis was used to explore the association between nutrient intakes and soya consumption, with cultural background, sex, age and economic status being included as covariates. On any given day, 3·3 % ( n 1085) of Canadians consume soya foods, with females, Asian Canadians and adults with post-secondary education being more likely to be soya consumers. As a whole, adolescent and adult respondents who had consumed at least one soya food during their 24 h dietary recall had higher energy intakes, as well as increased intakes of nutrients such as protein, fibre, vitamin C, vitamin B6, naturally occurring folate, thiamin, Ca, P, Mg, PUFA, Fe and K and lowered intakes of saturated fat. These data indicate that soya food consumption is associated with improved diet quality of Canadians. However, future research is necessary to investigate the association between increased energy intake and soya consumption.